Character Building Method: An approach to Improve the Discipline for Students in Higher Education - Susniwati Susniwati; Iin Agustina; Tuti Asmala; Kurniawati Kurniawati; Ani Surtiani (TGO Journal of Community Development, 2024)
This community service activity aims to evaluate the effectiveness of the Character Building program at Bandung University in enhancing student discipline. The methodology involves both quantitative and qualitative data analysis derived from surveys and interviews with students, program chairs, and academic personnel. The evaluation results indicate a significant improvement in student discipline, reflected in positive changes in behavior, increased participation in academic activities, and engagement in social projects. Students' awareness of discipline values and responsibility has also increased, creating a more positive academic atmosphere. This research implies that the character-building program is effective as a character-formation strategy, serving as a foundation for further development. The study also underscores the importance of direct student involvement in evaluation and emphasizes the need for ongoing monitoring to identify long-term changes. Practical implications include continuous improvement in program implementation and attention to various dimensions of the student experience.